Population dynamics of the yellowstripe scad (Selaroides leptolepis Cuvier, 1833) and Indian mackerel (Rastrelliger kanagurta Cuvier, 1816) in the Wondama Bay Water, Indonesia. (March 2018) - Sala, R; Bawole, R; Runtuboi, F; Mudjirahayu,; Wopi, I A; Budisetiawan, J; Irwanto,
Abstract: The Wondama Bay water is located within the Cendrawasih Bay National Park and is potential for fishery resources, including pelagic fish such as yellowstripe scad ( Selaroides leptolepis Cuvier, 1833) and Indian mackerel ( Rastrelliger kanagurta Cuvier, 1816). Yet, information about the population dynamics of these species in the region is unknown until today. Meanwhile, the fishing activities have been quite intensive and include the dominant catches over the last ten years by traditional fishermen fishing using liftnets. Therefore, this study aims to determine some of specific characteristics of the population dynamics and fish utilization status of scad and mackerel in the waters of the Wondama Bay. Data used in this study were taken from direct observation of catch of liftnet fishery. The data then were analysed by using FISAT II to estimate the growth parameters, mortality rates, and yield per recruitment. The results showed that yellowstripe scad has the positive allometric growth, while Indian mackerel followed isometric growth. Models of fish growth were L(t) = 22 (1-e -3.0(t-0.05) ) for yellowstripe scad and L(t) = 27.8 (1-e -4.0(t-0.04) ) for Indian mackerel. The natural mortality (M) of 4.19 year -1, fishing mortality (F) of 5.01 year -1, and total mortality (Z) of 9.20 year -1 were for yellowstripe scad, and M of 4.74 year -1, F of 2.52 year -1 and Z of 7.26 year -1 were for Indian mackerel. Based on the mortality rates, estimated exploitation rate for the yellowatripe scad was 54 % and the Indian mackerel was 35 %. To increase the production of catch without increasing fishing effort (fishing mortality) can be done by increasing the size of fish caught or the Lc/L∞ should be greater than 0.5.